Exploring Gas/Solid Interface Reactions of Solid Oxide Cell Electrodes via Model Thin‐Film Systems - Jinwook Kim; Hyunseung Kim; Seongwoo Nam; Yoonseok Choi; WooChul Jung (EcoMat)
ABSTRACT Solid oxide cells (SOCs) are promising energy conversion devices capable of efficiently converting electrical energy to chemical energy and vice versa. Enhancing efficiency and durability in SOCs necessitates a thorough understanding of the electrode's gas/solid interface, which is often hindered by the intricate structures of actual cells. Consequently, researchers have turned to thin‐film‐based model systems with well‐defined structures to advance this understanding. This review delves into the fundamental studies conducted using these systems to investigate phenomena at the electrode interfaces of SOCs. It systematically addresses how model electrodes are fabricated and assessed, along with the various phenomena that have been studied through these systems. Moreover, this review explores research areas within SOCs that require more in‐depth study, which can be facilitated by the use of thin‐film‐based model systems. In this review, we aim to underscore how simplified models can yield crucial insights into the interface dynamics of SOC electrodes, potentially steering the development of more efficient and stable SOCs.